Short Communication: Birth weight of a Holstein calf based on forefoot circumference - LIA BUDIMULYATI SALMAN; WILLYAN DJAJA; ASEP ANANG; HENI INDRIJANI; RUHYAT PARTASASMITA (Smujo International, 2017)
Salman LB, Djaja W, Anang A, Indrijani H, Partasasmita R. 2017. Birth weight of a Holstein calf based on forefoot circumference. Nusantara Bioscience 9: 367-370. Record of birth weight of Holstein calf can be used as consideration for selection. The purpose of this study is to determine the accuracy of birth weight based on regular measuring tape compared to Calf scale BW Tape. The records of calf’s birth weight were collected from 1370 female calf birth records from PT Taurus Dairy Farm, Sukabumi. Birth weight measurements were performed by (i) measuring birth weight using Calf scale BW Tape (Nasco, Fort Atkinson, WI); (ii) predicting birth weight with regression based on the circumference of the right front toenails using regular measuring tape a day after the calf was born; (iii) weighing the calf with the scales. The results showed that the predicted birth weight of dairy cow’s calves can be done by regular measuring tape with a polynomial regression equation, Y=(-6288,6)+(1378.8X)-(113.0X2)+(4.1X3)-(0.056X4), which has a deviation 0.5%, and 7.4% using Calfscale BW Tape. Conclusion of this research is that predicting birth weight of dairy cow’s calves using regular measuring tape is more accurate than using Calfscale BW Tape